Protective Effects of Curcumin and its Analogues via the Nrf2 Pathway in Metabolic Syndrome - Rajabi, Shahnaz; Darroudi, Majid; Naseri, Kobra; Farkhondeh, Tahereh; Samarghandian, Saeed (Current Medicinal Chemistry, 2024)
Metabolic Syndrome (MetS) refers to a set of medical conditions including insulin resistance, central obesity, atherogenic dyslipidemia, and hypertension. Due to these dysregulations, if not treated, MetS could increase the risk of CVA, CVD, and diabetes. As described by WHO, CVD is the leading cause of mortality in the world which motivates researchers to investigate the management of its risk factors, especially MetS. It is reported that oxidative stress secondary to the abundant generation of free radicals oxygen species (ROS) and the ensuing altered redox status play an important role as a mediator in MetS. As a result, using new antioxidant agents with higher bioavailability has been proposed as an efficient treatment. Curcumin (a polyphenol of the diarylheptanoids class), which is used as a traditional medicine for various diseases including cardiovascular diseases and diabetes, is characterized by its antioxidant properties which, at least in part, are mediated via the activation of the Nrf2/ARE signaling pathway. Nrf2 is a transcription factor that plays a key role in regulating internal defense systems and increases antioxidant levels to decrease oxidative damage and cell apoptosis. Nrf2 expression and stability are enhanced by curcumin, leading to a higher rate of Nrf2 migration to the cell nucleus to regulate ARE gene expression, thus protecting cells against oxidative stress. In this article, we provide a comprehensive review of the molecular effect of curcumin and its derivatives via Nrf2 regulation in several conditions, such as diabetes, hypertension, dyslipidemia, and obesity.
Keywords: Curcumin